2021
DOI: 10.3389/fmicb.2021.576696
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Analysis Demonstrated a Link Between Staphylococci Isolated From Different Sources: A Possible Public Health Risk

Abstract: Coagulase-negative staphylococci (CoNS) have been recovered from different ecological niches, however, little is known about the genetic relatedness of these isolates. In this study, we used whole genome sequencing to compare mecA positive (mecA+) Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus hominis isolates recovered from hand-touched surfaces from general public settings in East and West London with data of isolates deposited to European Nucleotide Archive (ENA) by other researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…For example, Cutibacterium acnes , which was notably abundant in the museum samples, is a well-known skin commensal-the most prevalent bacteria residing in human, healthy, sebum-rich skin areas such as the face and back [28] . Similarly, Staphylococcus aureus and Staphylococcus hominis , are also human-associated bacteria that thrive in indoor environments, and its presence in the museum samples align with previous studies reporting that staphylococci, usual colonisers of the human skin and upper respiratory tract, are commonly spread from humans to built environment surface and air [29][30][31] . Moraxella osloensis was reported to be the most abundant species across the exhibition samples, and is gram-negative aerobic bacterium that is considered to be an opportunistic human-associated pathogen, previously isolated from the upper respiratory tract, blood, genitourethral speciments, and other sites in humans [32][33][34] .…”
Section: Microbial Composition and Diversitysupporting
confidence: 85%
“…For example, Cutibacterium acnes , which was notably abundant in the museum samples, is a well-known skin commensal-the most prevalent bacteria residing in human, healthy, sebum-rich skin areas such as the face and back [28] . Similarly, Staphylococcus aureus and Staphylococcus hominis , are also human-associated bacteria that thrive in indoor environments, and its presence in the museum samples align with previous studies reporting that staphylococci, usual colonisers of the human skin and upper respiratory tract, are commonly spread from humans to built environment surface and air [29][30][31] . Moraxella osloensis was reported to be the most abundant species across the exhibition samples, and is gram-negative aerobic bacterium that is considered to be an opportunistic human-associated pathogen, previously isolated from the upper respiratory tract, blood, genitourethral speciments, and other sites in humans [32][33][34] .…”
Section: Microbial Composition and Diversitysupporting
confidence: 85%
“…Staphylococci, usual colonizers of the human skin and upper respiratory tract, are commonly spread from humans to BE surfaces and air [59][60][61]. Many staphylococcal species can become opportunistic pathogens and cause severe diseases including blood-stream, lung, soft tissue, and skin infections [62], but also atopic diseases such as asthma and hay fever [63].…”
Section: Staphylococcus Speciesmentioning
confidence: 99%
“…Only a few studies ( Cave et al, 2019 , Kang et al, 2018 , Roberts et al, 2013 , Shen et al, 2018 ) have focussed on general public settings in built-up environments but the studies that have been conducted generally shown that public settings have a high abundance of AMR resistance across different species. Some of these species pose a public health risk as they have genetic linkage to isolates that have caused infections in humans and livestock animals ( Cave et al, 2021 , Xu et al, 2018b , Zou et al, 2019 ). The main issues with many of these studies ( Conceição et al, 2013 , Zhou and Wang, 2013 , Kahsay et al, 2019 ) is that they tend to focus on relevant clinical bacteria (including those belonging to the genus Staphylococcaceae and Enterobacteriaceae ), recovered from surfaces and from the air: little is known about the diversity of antimicrobial resistant bacterial species and AMR genes present in public settings and the built environment around the globe, including how bacteria come to be in such environments and the main barriers or enablers of transmission and resistance emergence.…”
Section: The Threat From Antimicrobial Resistancementioning
confidence: 99%
“…There is only a limited number of studies on the prevalence of CoNS in non-healthcare public settings and the general built environment. These studies have investigated shopping centres ( Cave et al, 2019 , Cave et al, 2021 ), train stations ( Cave et al, 2019 , Cave et al, 2021 , Peng et al, 2015 , Xu et al, 2018b , Zhou and Wang, 2013 ), hotel rooms, supermarkets, restaurants, public transport, public libraries ( Xu et al, 2018b ), around the world; public restrooms ( Cave et al, 2019 , Cave et al, 2021 , Mkrtchyan et al, 2013 ) and public areas in hospitals in London, UK ( Cave et al, 2019 , Cave et al, 2021 ); university campuses in Thailand ( Seng et al, 2017 ), and the metro system in China ( Peng et al, 2015 , Zhou and Wang, 2013 ) and food markets in Assam, India ( Sivaraman et al, 2020 ).…”
Section: Antimicrobial Resistance Of Staphylococcus Aureusmentioning
confidence: 99%
See 1 more Smart Citation